Single Nucleotide Polymorphisms Associated with the Safety and Efficacy of Anti-Gout Medications (Precision Medicine Communications, 2022)
Gout has become more widespread during the last few decades. Gout is a kind of inflammatory arthritis that is accompanied by sporadic pain, inflammation, and swelling within joints as a result of the accretion of monosodium urate crystals. The global incidence of gout has mounted in developed countries and it has afflicted particular ethnic groups, for instance, South Pacific Island populations. Hyperuricemia, manifested by an amplified serum urate, is the key predictor of gout. The optimum concentration of serum urate is less than 6.8 mg/dl, whereas individuals with hyperuricemia have a serum urate of over 6.8 mg/dl. The effective treatment of gout is relative to the type of gout. Nevertheless, controlling the level of serum urate is central to effective gout management. Anti-inflammatory drugs are available to mitigate acute flares and inhibit inflammation. Additionally, urate-lowering therapies are available to dissolve crystals and avert gout flares. Genomic and experimental data suggest that genetic variants linked to gout disease are of pharmacogenetic relevance. Pharmacogenetics’ function in anticipating responses and adverse outcomes to gout therapy is of keen importance. In this study, we summarize the progression of gout disease, the complications of contemporary gout therapy, and the relationship between genetic variations and therapeutic outcomes of certain drugs used in the management of Gout.
Keywords: Gout; hyperurecemia; monosodium urate crystals; pathogenesis; treatment; pharmacogenetics